2020
DOI: 10.5194/acp-20-8047-2020
|View full text |Cite
|
Sign up to set email alerts
|

Marine productivity and synoptic meteorology drive summer-time variability in Southern Ocean aerosols

Abstract: Abstract. Cloud–radiation interactions over the Southern Ocean are not well constrained in climate models, in part due to uncertainties in the sources, concentrations, and cloud-forming potential of aerosol in this region. To date, most studies in this region have reported measurements from fixed terrestrial stations or a limited set of instrumentation and often present findings as broad seasonal or latitudinal trends. Here, we present an extensive set of aerosol and meteorological observations obtaine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 45 publications
(63 reference statements)
7
16
0
Order By: Relevance
“…3). Andreae (2009) found that the CCN 0.4 /CN ratios from a wide range of environments averaged 0.4, agreeing well with mid-latitude data from this study but highlighting the unique nature of the polar populations. Aerosol composition further south is dominated by sulfur-based particles, consistent with the established literature (e.g.…”
Section: Trajectory Analysessupporting
confidence: 86%
“…3). Andreae (2009) found that the CCN 0.4 /CN ratios from a wide range of environments averaged 0.4, agreeing well with mid-latitude data from this study but highlighting the unique nature of the polar populations. Aerosol composition further south is dominated by sulfur-based particles, consistent with the established literature (e.g.…”
Section: Trajectory Analysessupporting
confidence: 86%
“…Davison et al (1996) found maximum levels of DMS and methanesulfonic acid in aerosols in the seasonal sea ice region compared to open oceans further north. Other voyages have observed new particle formation events (Atkinson et al, 2012) and a previously unaccounted source of organic nitrogen in seasonal ice zone aerosol populations (Dall'Osto et al, 2017). These results suggest aerosol populations of the seasonal ice zones are distinct from those of the Antarctic continent and the mid-latitudes and upper latitudes of Southern Ocean.…”
Section: Introductionmentioning
confidence: 85%
“…The MICA (Mid-Infrared CAvity enhanced spectrometer, which is a prototype of a commercially available ABB Los Gatos OCS analyser) instrument measures OCS, carbon monoxide (CO) and CO 2 employing off-axis-integrated cavity output spectroscopy (OA-ICOS, Baer et al, 2002;O'Keefe et al, 1999;Paul et al, 2001). Air samples are internally pumped through a 305 mm long and 51 mm diame-ter cavity at a mass flow rate of about 6 × 10 −6 kg s −1 with the cavity pressure regulated to 80 hPa.…”
Section: Mid-infrared Cavity Enhanced Spectrometer -Micamentioning
confidence: 99%